Cultural Background and Technology Acceptance: Evaluation of ICT projects that bridge the digital divide
This study examines the effects of cultural background on the acceptation of Information and Communication Technology (ICT) in developing countries. It is a pilot study attempt to investigate whether cultural background values or other factors such as age, gender and education influence people's attitudes towards and acceptance of ICT. To this purpose, an ICT community development project in the south of India is studied. In the Netherlands, this study is replicated on a smaller scale. From the findings it seems that cultural background values have some influence on the acceptance process of ICT. However, a person's decision to accept technology and participate in an ICT skill development course was found to be influenced more strongly by the level of public promotion of the project. Besides that, actual use in developing countries was found to be related to age of the subjects.